Evaluating the food safety and risk assessment evidence-base of polyethylene terephthalate oligomers: Protocol for a systematic evidence map. (September 2022) - Schreier, Verena N.; Appenzeller-Herzog, Christian; Brüschweiler, Beat J.; Geueke, Birgit; Wilks, Martin F.; Simat, Thomas J.; Schilter, Benoit; Smieško, Martin; Muncke, Jane; Odermatt, Alex; Roth, Nicolas
Abstract: Background: Polyethylene terephthalate (PET) oligomers are ubiquitous in PET used in food contact applications. Consumer exposure by migration of PET oligomers into food and beverages is documented. However, no specific risk assessment framework or guidance for the safety evaluating of PET oligomers exist to date. Aim: The aim of this systematic evidence map (SEM) is to identify and organize existing knowledge clusters and associated gaps in hazard and exposure information of PET oligomers. Research needs will be identified as an input for chemical risk assessment, and to support future toxicity testing strategies of PET oligomers and regulatory decision-making. Search strategy and eligibility criteria: Multiple bibliographic databases (incl. Embase, Medline, Scopus, and Web of Science Core Collection), chemistry databases (SciFinder-n, Reaxys), and gray literature sources will be searched, and the search results will be supplemented by backward and forward citation tracking on eligible records. The search will be based on a single-concept PET oligomer-focused strategy to ensure sensitive and unbiased coverage of all evidence related to hazard and exposure in a data-poor environment. A scoping exercise conducted during planning identified 34 relevant PET oligomers. Eligible work of any study type must include primary research data on at least one relevant PET oligomer with regard to exposure, health, or toxicological outcomes. Study selection: For indexed scientific literature, title and abstract screening will be performed by one reviewer. Selected studies will be screened in full-text by two independent reviewers. Gray literature will be screened by two independent reviewers for inclusion and exclusion. Study quality assessment: Risk of bias analysis will not be conducted as part of this SEM. Data extraction and coding: Will be performed by one reviewer and peer-checked by a second reviewer for indexed scientific literature or by two independent reviewers for gray literature. Synthesis and visualization: The extracted and coded information will be synthesized in different formats, including narrative synthesis, tables, and heat maps. Systematic map protocol registry and registration number: Zenodo: https://doi.org/10.5281/zenodo.6224302.